An assessment of the frequency of blood transfusion before and after starting hydroxyurea therapy in children of sickle cell anemia - Gupta, Shikha; Chaudhary, Prachi; Chauhan, Amrita; Malpani, Preeti (Asian Journal of Medical Sciences, 2022)
Background: Hydroxyurea therapy is a known effective and safe therapy for the treatmentof sickle cell anemia (SCA). Although it is used worldwide in our Madhya Pradesh basedsetup, it is underutilized due to economic reasons and unaware practitioners about itsuse. Aims and Objectives: The Objective of the study is to assess the frequency ofblood transfusion year before and after starting hydroxyurea therapy in children of SCA. Materials and Methods: An ambispective observational study was performed at MGM Medical College Indore over a period of 1 year 8 months. One hundred and ninety patients were enrolled after taking a complete history, then started on Hydroxyurea and followed up every 2 months till 1 year. On follow-up, frequency of blood transfusion was noted along with routine investigations and for any side effects. Results: Of 190 total recruited patients, 84 were studied at the end because of loss to follow-up due to various reasons. Significant decrease in the need for blood transfusion was observed within 1 year of starting Hydroxyurea (P<0.05). Conclusion: The use of hydroxyurea in our native population at our setup can decrease the need for frequent blood transfusion in sickle cell patients.